Addition a New Species of Dicnecidia Diakonoff, 1982 (Lepidoptera: Tortricidae: Olethreutinae) from Thailand and a New Record of the Genus from Thailand and Laos - Thonongtor, Phawin; Pinkaew, Nantasak (Tropical Natural History, 2025)
Dicnecidia narathiwatensis Thonongtor and Pinkaew sp. nov. is described based on a single male specimen from Narathiwat Province, southernmost Thailand. In addition, D. fumidana Kuznetzov, 1997, previously recorded only from Vietnam, is recorded for the first time from Thailand and Laos. Illustrations of adults and genitalia are provided. The discovery of the new species increases the total number of described Dicnecidia to four.